SOLDIER CODE LANGUAGE IN THE MEMORY OF THE HISTORY OF VETERANS OF SEROJA BANYUWANGI 1765-1976 AND THE IMPLICATIONS FOR HISTORY SUBJECTS AND INDONESIAN: Bahasa Sandi Tentara Dalam Ingatan Sejarah Veteran Seroja Banyuwangi Tahun 1765-1976 dan Implikasinya terhadap mata Pelajaran Sejarah dan Bahasa Indonesia - Ahmad Sulthoni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This study aims to determine 1). History of the Republic of Indonesia's state ciphers; 2) know the code language used by Seroja Veterans in the history of defending Indonesia's independence; and 3). know the implications of coded language on History Education subjects and Indonesian Language Education subjects. This study used a qualitative approach with case study research methods and sociolinguistic theoretical methods. Data collection was carried out using physical observation techniques, interviews, and documentation. The result of the research is that the History of Encoding of the Republic of Indonesia cannot be separated from the role of dr. Roebiono Kertopati is the Father of Indonesian National Encryption. The code language used by Veterans has the following characteristics: short and concise, clear, firm, easy to understand for the recipient of the information, and the words used are simple. Veterans only receive codes according to the leadership's instructions. In general, the types of codes are animal codes, types of food, types of animals and others that are not permanent in nature. the implications of coded language for History Education subjects can be used as a source of learning history, historical awareness and historical research. For Indonesian language education subjects, it can be used to add a variety of vocabulary.